Bacterial communities associated with individual transparent exopolymer particles (TEP). (17th July 2019) - Zäncker, Birthe; Engel, Anja; Cunliffe, Michael
Abstract: Transparent exopolymer particles (TEP) are polysaccharide-rich microgels that are prevalent in the marine environment and have important roles in the aggregation of organic matter and carbon export from the euphotic zone. TEP are readily colonized by bacteria and utilized by specialized taxa, such as Alteromonadaceae. However, bacterial community composition specifically attached to natural TEP remains largely unknown. In this study, we isolated individual TEP from Plymouth Sound (UK) and performed DNA sequencing of the TEP-attached bacterial communities. We also sampled the cognate bulk seawater total bacterial communities for comparison. The bacterial communities associated with individual TEP showed distinct differences compared to the total bulk bacterioplankton communities, with Alteromonadaceae significantly more abundant on TEP. The TEP-associated Alteromonadaceae consisted of two operational taxonomic units that were closely related to Marinobacter and Glaciecola, both previously associated with biogenic aggregates and microgel-rich habitats. This study provides novel insight into marine bacterial–microgel interactions.